On the relationship between Mathematics- and Computer Science Education - Fuchs, Karl (Teaching Mathematics and Computer Science, 2024)
In the first half of the paper, the profile of the two scientific disciplines of Mathematics Education and Computer Science Education is traced. In Mathematics Education, the description has been given in a short longitudinal section of its preying cornerstones since the beginning of the 1960s. In Computer Science Education, this is done through the description of an emancipatory science that has been taking place since the beginning of the 1990s. The second half of the contribution, with the discussion of the different perspectives of the two disciplines on the common topics of modeling and competence models, finally leads to the identification of the two disciplines as two autonomous and independent sciences.